PENDAMPINGAN TERHADAP AKTIVIS DAKWAH DALAM MENGAKTUALISASIKAN NILAI-NILAI AJARAN AGAMA ISLAM - Dalmeri, Dalmeri (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Assistance to da'wah activities on an ongoing basis will provide a complete understanding of the year process and da'wah conveying religious teachings carried out by religious leaders as well as Ustadz and Ustadzah to instill moral values for today's Millennial young generation. The da'wah process is usually carried out with a well-organized plan to be carried out so that the pattern of teaching religious guidance can be understood by the Ummah and the community as well as Junior High School (SMP) students in the special Central Jakarta area and DKI Jakarta in general. Assistance by making systematic planning to change the perspective and insight of da'wah activists when providing an understanding of well-defined religious teachings. The mentoring process by making plans for da'wah activists consisting of Ustadz and Ustadzah, as well as Islamic Religious Education Teachers at the junior high school level by providing virtual training and providing direct training materials even with the implementation of strict Health Protocols so that they can be applied easily by them when doing da'wah activities to realize the values of religious teachings to the Ummah and Society, as well as junior high school students. The results of the mentoring and training turned out to have made da'wah activists have good insights and could be applied among the people and society, as well as junior high school students virtually due to the pandemic situation. Every mentoring process by making good plans is still carried out so that the da'wah orientation can provide a good understanding for the people and the community as well as junior high school students.